Protest Against Injustice Reflected In John Grisham's The Street Lawyer Novel (1998): A Marxist Criticism - Jelita, Fitra Ratna; , Dr. M. Thoyibi, M.S; , Titis Setyabudi, S.S. M. Hum (2014)
The major problem of this research is how protest against injustice reflected in John Grisham‟s The Street Lawyer novel. The objective of this research is to analyze the novel based on its structural element and to analyze the novel based on Marxist criticism. In analyzing The Street Lawyer novel, the researcher uses descriptive qualitative method and Marxist criticism. The data sources consist of primary data source and secondary data source. The primary data source is The Street Lawyer novel and the secondary data sources are taken from some books, websites, and other literary and other matters that support this analysis. The technique of the data collection is library research and the technique of data analysis is descriptive analysis. The outcomes of this research are as follows. First, based on the structural analysis of the novel, Grisham emphasizes that the novel has close relationship with the social condition of American society in the late of twentieth century. Second, based on the Marxist analysis,Grisham generally wants to describe the protest against injustice through The street lawyer.The Street lawyer novel shows that there is disparity between the rich and poor people inthe social condition of American society at the late of twentieth century. The poor people often get unjust treatment from the rich people who have an authority.